ANALISIS PARA PIHAK DALAM KERJA SAMA PENGEMBANGAN HASIL HUTAN BUKAN KAYU DI KABUPATEN PASAMAN BARAT - Irma Yeny; Retno Agustarini; Yetti Heryati (Jurnal Analisis Kebijakan Kehutanan, 2018)
The success in natural resources management highly depends on the involvement of stakeholders to take a part and actively participate in achieving the goal. The research aims to reveal the roles and relationships among stakeholders in the implementation of  NTFPs development collaboration in Pasaman Barat Regency. The study was conducted by using interview technique and observation on the activities performed. Data was analyzed by using stakeholder analyses. The results showed that there are 14 stakeholders having linkages with natural resource management, whereas five of them are already perfomed their responsibility in the implementation of the collaboration, while nine other have the potential to be engaged in the collaboration but their duties and functions are not related with the development of NTFPs. The stakeholders are classified into key, main and supporting stakeholder. The relationship among stakeholders is positive and  there is no potential conflict, however there is still unconnected relation among them. The low number of stakeholders involved, indicates lacking of understanding among the stakeholders resulting inefficiency in NTFPs development program. The stakeholders in the main and supporting parties should be encouraged by increasing their understanding and effectiveness, hence they could provide positive impact on the achievement of the objective of the collaboration.